THE STATE OF MONITORING METABOLIC INDICES IN PATIENTS WITH GASTROCANCEROGENESIS AND CHRONIC ATROPHIC GASTRITIS - Zhukov, V.; Vynnik, Yu.A.; Бєлєвцов, Ю.П.; Vasylyeva, I.M. (World of Medicine and Biology, 2013)
The investigation was designed to study the state of monitoring metabolic indices in patients with gastrocancerogenesis and chronic atrophic gastritis. The increased activity of alkaline phosphatase, lactate dehydrogenase, enolase with elevated level of gastrin in blood serum was observed in patients with chronic atrophic gastritis. The estimation of monitoring indices in patients with the second and the third stages of gastrocancerogenesis revealed the elevation of glucose, Мg2+ ions, urea, creatinine, triacylglycerols and decreased levels of cholesterol, total protein, and albumin in blood. Obtained data indicated that patients with gastrocancerogenesis. The highest changes of monitoring indices dysfunction were observed in patients with the fourth stage of gastrocancerogenesis.
Keywords: gastrocancerogenesis; gastric cancer; chronic atrophic gastritis